Designing Interactive Online Atlas of Mammalian Anatomy (Cavia cobaya) - Muhammad Ja'far Luthfi; Riyanto Riyanto (Biology, Medicine, & Natural Product Chemistry, 2025)
This research is an integration between fields of Biology, Photography, Design, and Informatics Engineering. The study aimed to develop an interactive online atlas of mammalian anatomy to improve the accessibility and data sharing (free access) of mammalian anatomy. Website was developed using SDLC (System Development Life Cycle) which consists of five steps as follows: website’s strategic planning, determine the scope of website, website’s requirements analysis, design and implementations of website, and testing. Based on the results of testing and system implementation, it can be concluded that online interactive atlas (AtlasAnatomy.org) had been successfully built as anatomical educational media of mammal.